2013
DOI: 10.1002/stem.1429
|View full text |Cite
|
Sign up to set email alerts
|

Somatic loss of p53 leads to stem/progenitor cell amplification in both mammary epithelial compartments, basal and luminal

Abstract: Mammary epithelium comprises a layer of luminal cells and a basal myoepithelial cell layer. Both mammary epithelial compartments, basal and luminal, contain stem and progenitor cells, but only basal cells are capable of gland regeneration upon transplantation. Aberrant expansion of stem/progenitor cell populations is considered to contribute to breast tumorigenesis. Germline deletions of p53 in humans and mice confer a predisposition to tumors, and stem cell frequency is abnormally high in the mammary epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…Our results are consistent with those reported in the mammary gland and bladder in which the growth of p63+ cells is inhibited by Notch signaling (Bouras et al, 2008). Aberrant expansion of stem/ progenitor cell populations contribute to tumorigenesis (Chiche et al, 2013;Lim et al, 2009). Thus, failure of mechanisms that prevent abnormal expansion of p63+ basal cells in the airway epithelium could also play a role in lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with those reported in the mammary gland and bladder in which the growth of p63+ cells is inhibited by Notch signaling (Bouras et al, 2008). Aberrant expansion of stem/ progenitor cell populations contribute to tumorigenesis (Chiche et al, 2013;Lim et al, 2009). Thus, failure of mechanisms that prevent abnormal expansion of p63+ basal cells in the airway epithelium could also play a role in lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, K5-driven Cre expression should lead to excision of the conditional floxed allele from the entire mammary epithelium, which is consistent with our LacZ reporter assays (Fig. S1 A and B) and those of others (30) who showed that LacZ is expressed in all basal cells and most luminal cells in the mammary epithelium. K5-Cre Tg/+ should therefore induce mammary tumors with both luminal and basal cell origins.…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 91%
“…The two major subtypes we identified were luminal A and basal-like tumors, suggesting that transposon mutagenesis is occurring in all mammary epithelium cell populations. Consistent with this, studies in K5Cre transgenic mice have identified Cre activity in early mammary cell progenitors (30). K5Cre should therefore inactivate Pten and activate SB transposition in both luminal and basal cell progenitors and might explain the development of different breast cancer subtypes in our SB mouse model.…”
Section: Discussionsupporting
confidence: 81%
“…Other potential transcriptional regulators of MaSCs include the transcription factors Stat3, CCAAT/enhancer-binding protein-b, and c-myc, all of which affect mammary repopulating ability in vivo (LaMarca et al 2010;Staniszewska et al 2012;Moumen et al 2013). Conversely, the tumor suppressor p53 serves a critical role in restricting the renewal of MaSCs and regulating their asymmetric division (Cicalese et al 2009;Chiche et al 2013). …”
Section: Molecular Regulators Of Mascsmentioning
confidence: 99%